Different Methodological Approaches to Studying the Economic Effects of Cruise Tourism: The Case of Poland - Piotr NOWACZYK (Communications of International Proceedings, 2025)
Research uses different ways to estimate the economic effects of cruise tourism. The literature does not highlight the differences that exist between them. This can affect the results of research and mislead readers. The article presents all possible methodologies for estimating economic effects, i.e. based on tourist spending and based on seaport. Each of the above methodologies was presented separately for the home port and the port of call. The direct effect was determined using a survey, while the indirect and induced effects were determined using the input-output method. The direct effect takes the smallest values in the methodology based on the sea port of call. Only the expenditures of the tourist unit are taken as the direct effect. On the other hand, the direct effect has the highest significance in the methodology based on the tourist expenditures of the home port. In this case, the direct effect is taken as the tourist expenditures related to the arrival at the port and the expenditures made in the local economy. The indirect effect, on the other hand, takes the largest values in the methodology based on the seaport. They also depend on the degree of development of the economy of the study area and the way the national input-output table is regionalized. While there are differences in the effects in the methodologies studied, they do not affect the final result, which is the importance of cruise tourism to the economy. Future research on cruise tourism should take place with clearly defined effects.
Keywords: cruise tourism; economic effects; seaport; input-output method